The study of drug resistance characteristics and molecular typing of Salmonella enteritidis in Lanzhou City from 2019 to 2021 - MAO Xue; ZHANG Lianmei; WANG Yuhong; WANG Yan; CHENG Hui; ZHANG Jijun; DI Mengjie; LIU Lu (Zhongguo shipin weisheng zazhi, 2024)
ObjectiveTo provide scientific value for effective prevention of Salmonella infection and treatment， the drug resistance spectrum and drug resistance characteristics of Salmonella enteritidis in Lanzhou was exploreed and a database of some genotypes of Salmonella was established.MethodsA total of 94 strains of Salmonella were isolated from foodborne active surveillance in Lanzhou from 2019 to 2021 by serotyping and biochemical analysis. The drug resistance of 41 strains of Salmonella enteritidis was detected by drug susceptibility testing and pulsed field gel electrophoresis. BioNumerics （Version 7.6） software was used to cluster the PFGE profiles of 41 strains of Salmonella enteritidis.ResultsA total of 94 strains of Salmonella could be classified into 20 serotypes， with Salmonella enteritidis as the dominant serogroup， accounting for 43.62% （41/94）. 41 strains of Salmonella enteritidis were generally resistant to quinolone nalidixic acid bacteria （100.00%）， followed by up to 80.49%（33/41） resistance to penicillin ampicillin， the resistance rate to cefazolin was 39.02%（16/41）， and the resistance rates to ampicillin/sulbactam and tetracycline were 31.71%（13/41）. But the drug resistance rates were all 0.00% to imipenem and cefoxitin. Twenty-six （63.41%） of the strains showed multi-drug resistance， resulting in eighteen multi-drug resistance profiles. Lastly， A total of 19 bands were obtained by Xba Ⅰ digestion of 41 strains of Salmonella enteritidis， and the similarity between the bands was 74.20%~100.00%. The number of strains contained in each band type was different， and the homology between strains of the same year was highly and they have 100.00% identical bands.ConclusionSalmonella serotypes in Lanzhou are diverse and PFGE band types are complex， and its dominant serogroup Salmonella enteritidis is highly resistant and multi-drug resistant seriously.